Domains of case changing and case maintaining movements - Newson, Mark; Szécsényi, Krisztina (LingBaW. Linguistics Beyond and Within, 2022)
With recent developments in Case Theory, movements in which a DP acquires a different case to the one it would have received had it not moved have been accepted as a possibility. In this paper we examine a number of such movements from a variety of languages to attempt to characterise and understand them more fully. Based in Dependent Case Theory, our analysis claims that case change does not really happen, but case assignment is allowed to be delayed under certain circumstances creating the illusion of one case over-writing another. In explicating these circumstances, we are not only able to provide a better understanding of when ‘case change’ can and can’t happen, but also develop the theory in ways which address certain conceptual problems that it faces.